Comparison of running characteristics and heart rate response of international and national female rugby sevens players during competitive matches - Portillo, J.; Gonzalez-Rave, J. M.; Juarez, D.; Garcia, J. M.; Suarez-Arrones, L.; Newton, R. U. (The Journal of Strength and Conditioning Research, 2014)
This study compared the activity profile of national and international female rugby sevens players during competitive matches. Twenty rugby sevens female players were recruited, 10 were members of the Spanish National Team (26.27 ± 4.05 years, 65.39 ± 5.01 kg, 166.72 ± 6.70 cm) and 10 were amateur athletes from a Spanish rugby championship (32.12 ± 6.40 years, 66.48 ± 5.38 kg of body mass, 167.37 ± 3.02 cm). Data collection was conducted over 4 matches in each of the 2 tournaments, national and international. Distance, velocity, and heart rate (HR) were recorded using global positioning system devices for all participants throughout each match. There were significant differences (p < 0.01) in total distance (1642 ± 171 vs. 1363 ± 222 m), average speed (6.0 ± 0.3 vs. 5.2 ± 0.6 km/h), number of sprints (6.1 ± 3.1 vs. 1.9 ± 1.4 sprints), and distance covered in sprinting (118.8 ± 61.4 vs. 47.0 ± 38.8 m). Significant differences were found at >95% maximum HR (HRmax), both for the first (p < 0.01) and second half (p < 0.05). The work-rest ratio was significantly different (p < 0.01) between international (1:0.3) and national players (1:0.4). Significant differences were found in accelerations above 2 m/s^2 in the first and second half between the 2 groups. These findings suggest that distance covered in a match and speed are considerably different between international and national rugby sevens players, and this is reflected as higher intensity of play with consequently higher HR. Coaches may use this information to design specific running drills for this athlete population to match the requirements of national or international game play.